Clinical outcomes of staff training in positive behaviour support to reduce challenging behaviour in adults with intellectual disability: cluster randomised controlled trial. (12th February 2018) - Hassiotis, Angela; Poppe, Michaela; Strydom, Andre; Vickerstaff, Victoria; Hall, Ian S.; Crabtree, Jason; Omar, Rumana Z.; King, Michael; Hunter, Rachael; Biswas, Asit; Cooper, Viv; Howie, William; et al.
Abstract : Background: Staff training in positive behaviour support (PBS) is a widespread treatment approach for challenging behaviour in adults with intellectual disability. Aims: To evaluate whether such training is clinically effective in reducing challenging behaviour during routine care (trial registration: NCT01680276). Method: We carried out a multicentre, cluster randomised controlled trial involving 23 community intellectual disability services in England, randomly allocated to manual-assisted staff training in PBS ( n = 11) or treatment as usual (TAU, n = 12). Data were collected from 246 adult participants. Results: No treatment effects were found for the primary outcome (challenging behaviour over 12 months, adjusted mean difference = −2.14, 95% CI: −8.79, 4.51) or secondary outcomes. Conclusions: Staff training in PBS, as applied in this study, did not reduce challenging behaviour. Further research should tackle implementation issues and endeavour to identify other interventions that can reduce challenging behaviour. Declaration of interest: None.